La gouvernance des biens communs - Clément Mabi; Françoise Massit-Folléa (Communication)
Extending the Vox Internet research program, the authors question whether the efforts for a better coordination of climate issues management implemented in the 1980s can enrich the ongoing debate on the constitution of open, transparent and democratic Internet governance. Their working hypothesis argues that it is possible to isolate invariants within multi-stakeholder governance processes in different contexts and consequently to identify inputs and outcomes specific to the management of common goods.